Identification and assessment of glucose transporters SGLT1 and GLUT2 and incretin GLP-1 in the small intestine of guinea pigs (cavia porcellus) - Anglas P., Juan (2012)
The aim of this study was to identify and assess the presence of glucose transporters SGLT1 and GLUT2 and incretin GLP-1 in the small intestine of guinea pig (Cavia porcellus). Five animals of 90 days old were used. Samples from the duodenum, jejunum and ileum were collected after slaughtering to carry out immunohistochemistry assays. Expression of SGLT1, GLUT2 and GLP-1 was observed in all three portions of the small intestine, where SGLT1 showed the highest expression, with a strong staining intensity in the apical and medium section of the crypt-villus axis. GLUT2 showed a strong staining intensity throughout the crypt-villus axis in the jejunum. GLP-1 expression was indirectly analyzed by calculating the number of L cells per mm2 of intestinal mucosa, resulting that the jejunum had the largest number (8.46 ±1.16 cells/mm2) (p<0.05). The results suggest that SGLT1 glucose transporter would be the most important in the guinea pig, and unlike other species, GLP-1 may be mostly secreted by the jejunum.